2012
DOI: 10.1111/j.1445-2197.2012.06202.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with histologically proven acute acalculous cholecystitis

Abstract: AAC more commonly occurs in older patients and those with COAD. The operative outcomes and complications of AAC treated by cholecystectomy are similar to cases of acute calculous cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
(25 reference statements)
2
4
1
1
Order By: Relevance
“…The 7.04% occurrence rate of AAC in this study was similar to that reported in the previous series using similar criteria for AAC. 7,12 However, several studies reported a higher incidence of AAC than that in the present study. 9,11 Most of the studies used identical diagnostic criteria for AAC to this study, such as no stones or sludges in the gallbladder on imaging or pathological findings, although the diagnostic criteria of AC were different among studies.…”
Section: Factorscontrasting
confidence: 78%
See 2 more Smart Citations
“…The 7.04% occurrence rate of AAC in this study was similar to that reported in the previous series using similar criteria for AAC. 7,12 However, several studies reported a higher incidence of AAC than that in the present study. 9,11 Most of the studies used identical diagnostic criteria for AAC to this study, such as no stones or sludges in the gallbladder on imaging or pathological findings, although the diagnostic criteria of AC were different among studies.…”
Section: Factorscontrasting
confidence: 78%
“…We obtained a similar AAC occurrence rate to previous studies where AC was diagnosed pathologically, accordingly the TG18 diagnostic criteria could be equal to the pathological diagnosis. 7,12 Yokoe et al reported the distribution of the TG severity grade in their Japan-Taiwan collaborative study of AC and showed 36.4%, 46.0%, and 17.6% of patients were diagnosed as Grade I, II, and III, respectively. 19 This severity grade is equivalent to that of AAC patients in the present study.…”
Section: Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all the AAC patients were found to have atherosclerotic vascular-associated diseases, such as hypertension, diabetes, apoplexy, or ischemic heart disease. Studies have shown that atherosclerosis and increased blood viscosity in the elderly aggravates the ischemia of the gallbladder wall (23). In particular, diffuse damage to the wall of small blood vessels, which narrows and obstructs the arterial lumen, and damage to gallbladder mucosa significantly increase the risk of AAC (16,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…La CAA se ha asociado a mal pronóstico por el retraso en el diagnóstico y tratamiento, así como a la presentación en pacientes graves o con co-morbilidades [33][34][35][36] . De las publicaciones disponibles, es evidente que la CAA puede presentarse en niños aparentemente sanos 37 , en pacientes con patologías médicas [38][39][40] y quirúrgicas 41 , en infecciones graves de distinta etiología [42][43][44] , como también en infecciones banales 45 .…”
unclassified